Empowering Rural Women Entrepreneurs: Insights from Bihar’s Agricultural and Small Enterprises - Qurie Kumari; Souvik Ghosh; Swagat, Swagat Ranjan Rath (Indian Journal of Extension Education, 2025)
Farm women play an important role in agrarian economy. This study aimed to explore the role of entrepreneurship in empowering rural women in an eastern Indian state of Bihar, where literacy rates are low and socio-economic opportunities are limited. The research was conducted in Bhagalpur district during 2019-20, covering a random sample of 80 women entrepreneurs, 20 each engaged in mushroom cultivation, goat rearing, dairy farming, and stitching enterprises. Using the social empowerment as well as women empowerment in agriculture index, as a composite measure, this study assessed empowerment across social dimensions- personal autonomy, family decision-making, and political autonomy as well as agro-economic dimensions- production, resources, time, leadership, and income. Among the enterprises studied, mushroom entrepreneurs demonstrated the highest levels of empowerment across most of the social and agro-economic dimensions, followed by stitching entrepreneurs. The goat rearing and dairy farming entrepreneurs were lagged with respect to social and agricultural empowerment, respectively. The stepwise regression revealed that innovativeness, decision making ability, level of education and planning ability explained 39% variation in overall empowerment of women entrepreneurs. These aspects require to be considered for focused policy initiatives to promote entrepreneurship for the rural women